Deriving optical constants of volcanish ash using measurements from the planetary emissivity laboratory at DLR - Helbert, Jörn; Maturilli, Alessandro; Roush, Ted; Mannstein, Herrmann (2011 3rd Workshop on Hyperspectral Image and Signal Processing: Evolution in Remote Sensing (WHISPERS), 2011)
Using reflectance measurements of seven volcanic ash samples from the Eyjafjallajökull eruption in 2010 collected in different locations on Iceland we have started to derive optical constants. We present here initial results for one of the volcanic ash samples collected at Seljavellir farm, Iceland. The results will help in modeling the optical behavior of volcanic ashes. At the same time we could extend the capabilities of the Planetary Emissivity Laboratory in Berlin and offer yet another dataset to the scientific community.